Circadian clocks, brain function, and development. (December 2013) - Frank, Ellen; Sidor, Michelle M.; Gamble, Karen L.; Cirelli, Chiara; Sharkey, Katherine M.; Hoyle, Nathaniel; Tikotzky, Liat; Talbot, Lisa S.; McCarthy, Michael J.; Hasler, Brant P.
Abstract : Circadian clocks are temporal interfaces that organize biological systems and behavior to dynamic external environments. Components of the molecular clock are expressed throughout the brain and are centrally poised to play an important role in brain function. This paper focuses on key issues concerning the relationship among circadian clocks, brain function, and development, and discusses three topic areas: (1) sleep and its relationship to the circadian system; (2) systems development and psychopathology (spanning the prenatal period through late life); and (3) circadian factors and their application to neuropsychiatric disorders. We also explore circadian genetics and psychopathology and the selective pressures on the evolution of clocks. Last, a lively debate is presented on whether circadian factors are central to mood disorders. Emerging from research on circadian rhythms is a model of the interaction among genes, sleep, and the environment that converges on the circadian clock to influence susceptibility to developing psychopathology. This model may lend insight into effective treatments for mood disorders and inform development of new interventions.